Microleakage study of simplified adhesive systems in class V cavities of primary teeth - Anahita Haratian; Mehrdad Kazemian; Shiva Mortazavi; Pouran Samimi (Isfahan University of Medical Sciences, 2011)
Introduction: There is a high demand for tooth-colored restorations in pediatric dentistry. Since etch-and-rinse adhesive systems are time-consuming, there is a tendency to replace them with simplified adhesive systems. This study compared microleakage of class V composite resin restorations in primary teeth restored using simplified adhesive systems.Materials and Methods: In this in vitro study standard class V cavities were prepared in 60 primary canines with incisal margins in enamel and gingival margins in dentin. The samples were randomly divided into 4 groups and restored as follows: Group 1: Opti Bond Solo Plus (OBP); Group 2: Clearfil SE Bond (SEB); Group 3: Clearfil S3 Bond (S3B); Group 4: Xeno IV (XeIV). The cavities were filled with Filtek Z250 composite resin and observed under a stereomicroscope at × 32 for microleakage scoring. The results were analyzed with Kruskal-Wallis test followed by Mann-Whitney and Wilcoxon Signed Rank tests using SPSS software.Results: The results showed significant differences between groups 1 and 4 and group 3 in enamel leakage (p value = 0.005). There was also a significant difference between group 1 and groups 2 and 4 in dentinal leakage (p value = 0.001). The test showed that enamel leakage in groups 1 and 4 was significantly lower than dentinal leakage in these groups.Conclusion: The strong acidic adhesives in groups 1 and 4 were more effective in enamel leakage prevention. The mild self-etching adhesive in group 3 was effective in enamel and was the best in dentin leakage prevention. Key words: Microleakage, Simplified adhesives, Self-etching adhesive, Cervical cavity, Primary teeth.